The impact of stakeholder integration on large-scale, innovative PPP infrastructure projects - ALBALOOSHI, HOORIAH AHMED (2020)
Public-Private Partnerships (PPPs) are recognized as a viable option when procuring public services and infrastructure projects. In recent years, PPPs have become one of the most effective methods adopted by governments across the world, both in high-income and low and middle-income countries, these projects involved multiple stakeholders with varying interests and power in projects. United Arab Emirates recognized the importance of PPP project, therefore for the country began to legalize this practice and develop policies and procedures to facilitate the government and private sectors relationships and ensure the success of PPP projects. An example of this is the cabinet resolution No1/1 of 2017 and the Local Law of the Emirate of Dubai No.22 of 2015. The thesis focused on single case study that helped to explore and define how to ensure stakeholders integration in innovative PPP projects. PPPs have received attention from researchers and practitioners for their effects and associated risks on projects and participating parties and the crucial role of the stakeholders in PPP projects that affect project outputs, outcomes, and impacts. Much research has addressed the success factors of public and private sector projects and related challenges where a set of common factors have been identified, including stakeholder management factor. Examples of failed PPP projects indicate that some of the projects failed due to stakeholder related issues such as stakeholders’ knowledge, experience, and engagement. Despite the importance of stakeholder management in PPP projects, it has not yet received significant attention, this thesis seeks to address this gap in our current knowledge by holistically examining stakeholder integration (SI) in PPP innovative projects, as the integration of stakeholders between all parties is essential to the success of PPP projects, especially if it is innovative. SI is determined by a set of factors that must be integrated in equal measure to ensure the success of projects and conformity to organizational requirements and objectives. In addition to the importance of spreading knowledge and benefiting from experiences through harnessing the agreements between government and private agencies to implement these projects This study adopted qualitative research methodology to collect data through the conduct of a single case study of a cancelled PPP project based on a BOT contract in the UAE, which had been at the planning phase for more than eight years. The case study involved document analysis, participation observation, structure interviews, and semi-structured interviews with private sector representatives, members of local governments, members of the federal government, and sub-contractors and consultants. The main findings revealed that there are factors related to the extent of integration of stakeholders in the project that affect the success of these projects, such as knowledge, skills, experience, powers & interest between government organizations according to phases of the project as well as the unified PM tools, process and procedure in governments in innovative large-scale project management. Also, the findings reveal that the absence of procedures and laws in such projects causes a large number of obstacles that lead to the failure of these projects and not to take advantage of the opportunity associated with this kind of projects. The key contributions to knowledge included bridging the gap in the literature related to the importance of stakeholder in delivering successful PPP project by considering factor that shape the level of integration between the two parties specifically and others. In addition, this empirical study focused on SI in large-scale innovative infrastructure PPP projects, which will fill the gap of defining the impact and the importance of SI in these fields. Based on the findings the study came up with a set of six variables that defines the Stakeholder integration: Knowledge; experience; skills; legal awareness; unified process and procedures and unified project management tools. Also the a framework was developed to highlights the required process and decision in managing PPP project in the earlier stages of the project with the case of the absence of process, law and the lack of experience, the framework was validated by industry experts to ensure that this new framework will provide local government organizations with a valuable basis for planning, implementing and evaluating the successful delivery of PPP projects.